Scaling data analysis with Apache Mahout - Drost, Isabel; Safari eBooks; O'Reilly strata making data work conference (2011 : Santa Clara, Calif.) ([United States?] : O'Reilly Media, 2011)
"With growing amounts of digital data at the fingertips of software developers, the need for a scalable, easy to use framework is tremendous. This talk introduces Apache Mahout--a project with the goal of implementing scalable machine learning algorithms for the masses." --Resource description page.
Title from title screen.
Recorded at O'Reilly strata making data work conference: Feb. 1-3, 2011, Santa Clara, Calif.
Electronic reproduction.
Keywords: Machine learning; Web site development; Electronic books